Reinterpretasi Ayat-ayat Kekerasan - Lina Aniqoh (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2018)
This paper seeks to elaborate on the textual interpretation of Q.S Muhammad verse 4 and Q.S at Taubah verse 5. These two verses are often employed by the extremist Muslim groups to legitimize their destructive acts carried out on groups considered as being infidels and as such lawfully killed. The interpretation was conducted using the double movement hermeneutics methodology offered by Fazlur Rahman. After reinterpretation, the two verses contain moral values, namely the war ordered by God must be reactive, fulfill the ethics of